Service Learning Course in the Engineering Curriculum:EPICS - Irfan, M. M.; Sammaiah, P. (Journal of Engineering Education Transformations, 2025)
In the quest for approaches to recreate "real" configuration experiences in our classrooms, the model of community service learning is frequently ignored within educational curriculum. It is, however, a powerful model for learning the engineering design process. SR Engineering College introduced the EPICS - Engineering Projects in Community Service as an elective course in the curriculum. This academic credit based course is highlighted with its objectives and some projects are illustrated to give complete awareness about the course modules. The projects selected illustrate: mechanical, civil, electrical, hardware and software design in the context of service learning. A discussion of how the Program Objectives align with the National Board of Accreditation's Outcome Based Education (NBA's OBE) criteria is also included.